2020
DOI: 10.1177/0885066620984410
|View full text |Cite
|
Sign up to set email alerts
|

After-Hours/Nighttime Transfers Out of the Intensive Care Unit and Patient Outcomes: A Systematic Review and Meta-Analysis

Abstract: Purpose: We evaluated the effects of after-hours/nighttime patient transfers out of the ICU on patient outcomes, by performing a systematic review and meta-analysis (PROSPERO CRD 42017074082). Data Sources: MEDLINE, PubMed, EMBASE, Google Scholar, CINAHL, and the Cochrane Library from 1987-November 2019. Conference abstracts from the Society of Critical Care Medicine, American Thoracic Society, CHEST, Critical Care Canada Forum, and European Society of Intensive Care Medicine from 2011-2019. Data Extraction: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…A review article supports this finding, noting an increased risk for readmissions to ICUs related to transfers during evening and nighttime (Elliott et al, 2014 ). Another review and meta‐analysis showed that after‐hours transfers were associated with increased in‐hospital mortality, ICU readmission and length of hospital stay (Moshynskyy et al, 2022 ). Consequently, international recommendations state that patient transfer should preferably happen during the daytime (National Institute for Health and Care Excellence, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A review article supports this finding, noting an increased risk for readmissions to ICUs related to transfers during evening and nighttime (Elliott et al, 2014 ). Another review and meta‐analysis showed that after‐hours transfers were associated with increased in‐hospital mortality, ICU readmission and length of hospital stay (Moshynskyy et al, 2022 ). Consequently, international recommendations state that patient transfer should preferably happen during the daytime (National Institute for Health and Care Excellence, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moshynskyy et al (28) and Yang et al (29) reported that nighttime transfers from the ICU were associated with higher hospital mortality. A systematic review and meta-analysis by Vollam et al (17) showed that out-of-hours discharge from ICU was significantly associated with hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it is likely that the improper ratio of nursing staff limited the attainment of high SSC 1-h bundle, thus increasing the death of patients with sepsis. Moshynskyy et al (28) and Yang et al (29) reported that nighttime transfers from the ICU were associated with higher hospital mortality. A systematic review and meta-analysis by Vollam et al (17) showed that out-ofhours discharge from ICU was significantly associated with hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…NSM provides the guidance needed to prevent stress and the subsequent negative impact on the health of CMC. Frequent stressors for patients and CMC transferring from the ICU to the general acute care unit include inconsistent and inadequate handoff between nurses, incomplete medication reconciliation, rapid alterations in sedation, and timing of the patient transfer (Blazin et al, 2020; Duceppe et al, 2019; Herbst et al, 2018; Moshynskyy et al, 2022; Österlind et al, 2020).…”
Section: Nursing Implicationsmentioning
confidence: 99%